Hemifacial Spasm Due to Contralateral Supratentorial Tumor: A Case Report - Nugraha, Priya; Puti, Nazla Ananda Rachmi; Hamdan, Muhammad (AKSONA, 2025)
Highlight: A rare case of hemifacial spasm due to contralateral supratentorial tumor. Improvement of hemifacial spasm after tumor removal treatment. A comprehensive patient examination can establish the correct diagnosis and treatment.   ABSTRACT Introduction: A rare neurological disorder known as hemifacial spasm (HFS) is characterized by involuntary, unilateral facial muscle contractions, typically caused by facial nerve irritation. In this report, we looked at a rare and fascinating case of hemifacial spasm (HFS) caused by a large contralateral supratentorial meningioma. The HFS went away amazingly after the tumor was removed and the patient was treated with corticosteroids. The complex connection between neurological disorders and intracranial tumors is highlighted in this case, along with potential treatment approaches for the patient. Cases: A 48-year-old woman complained of uncontrolled movements and spasms in her right eyelid and right lip corner for the past two years. The symptoms were accompanied by headaches, cognitive impairment, and a history of syncope. A neurological examination revealed right-sided central facial palsy. An MRI revealed a large atypical meningioma in the left frontal lobe. This resulted in significant brain displacement and perifocal edema, but no neurovascular contact with the 7th cranial nerve. Her hemifacial spasms significantly decreased following surgical resection, even with medication reduction. Conclusion:As an uncommon manifestation of contralateral supratentorial tumors, HFS requires careful evaluation of the patient’s history, physical examination, and radiological findings, as well as consideration of a wide range of potential causes. Accurate diagnosis and effective management can help reduce the risk of poor prognosis.